The nature and enactment of African dance that produces neurogenic tremors - Toto, Sivuyisiwe (Division of Occupational Therapy, 2022)
Distinctly African health-promoting human occupations are under-researched in occupational therapy. Many occupational therapy interventions used in South Africa have been developed elsewhere and may be inaccessible to many. African dance that produces neurogenic tremors (ADNT) is an occupation that may already be accessible to many, and a potential resource for health and could be used in occupational therapy. Research Question: What is the nature and enactment of ADNT? Aim: The study aimed to explore, describe and explain the nature and enactment of ADNT among professional dancers in Cape Town, South Africa. Research objectives: To explore the perceived temporal, spatial and sociocultural conditions conducive for ADNT. To describe and explain the enactment of ADNT in terms of format, pace, and the sequence of steps involved in performing African dance repertoires that are known to produce neurogenic tremors. To describe the experience of those who participate in ADNT by exploring the subjective effect it has had on stress levels or during stressful periods. Methodology: Case study methodology was used. Semi-structured interviews, focus groups, and participant observation were the data collection methods used. Thematic analysis was employed to analyse the data. Findings: Four themes emerged from the study (1) Triggers: Improvisation, Energy and pushing beyond limits. (2) Essence of self: Embodying Africa through dance. (3) Leaving and returning to the body and (4) Creatures of the soil: Connected to the ground and beyond…for health. Discussion: ADNT is healing, relational, transcendent, and contextually situated. It facilitates self-acceptance (ubuwena) through embodying Africa (KwaNtu) and holds potential to promote social cohesion (ubuntu). It is mainly enacted through improvisation (on and off-stage), through which socio-historical-cultural intergenerational resources (isintu) embedded within, are tapped into. ADNT offers opportunities for connectedness with the self, other people, as well as with transcendent beings. Conclusion: This study has illuminated the nature of ADNT as an extraordinary human occupation that offers participants instances of personal and collective meaning-making, healing, and transcendence. Transcendence is proposed as a source of personal and shared meaning.